1988
DOI: 10.1002/1097-0142(19880815)62:4<730::aid-cncr2820620415>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Availability of tumor-antigen 4 as a marker of squamous cell carcinoma of the lung and other organs

Abstract: The serum level of tumor-antigen 4 (TA-4) was measured in 401 patients with squamous cell carcinoma (SCC) of various organs (76 lung, 82 esophagus, and 234 head and neck). The mean serum level of TA-4 in patients with lung SCC was 3.6 times higher than that in healthy controls and even higher in the advanced stages of disease (III, IV). In patients with benign diseases or other types of lung cancer, however, the TA-4 serum level was not different from the controls regardless of the clinical stage. During radia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0
2

Year Published

1990
1990
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 6 publications
1
41
0
2
Order By: Relevance
“…The serum level of SCCA is increased in parallel to the growth of the tumour size or the recurrence of the disease. Therefore, measurement of the serum level of SCCA has been used clinically for the diagnosis and the management of SCC of the uterine cervix as well as other various organs (Kato et al, 1982(Kato et al, , 1983Maruo et al, 1985;Mino et al, 1988;Brioschi et al, 1991).…”
mentioning
confidence: 99%
“…The serum level of SCCA is increased in parallel to the growth of the tumour size or the recurrence of the disease. Therefore, measurement of the serum level of SCCA has been used clinically for the diagnosis and the management of SCC of the uterine cervix as well as other various organs (Kato et al, 1982(Kato et al, , 1983Maruo et al, 1985;Mino et al, 1988;Brioschi et al, 1991).…”
mentioning
confidence: 99%
“…This was confirmed in the present study when the conventional RIA method was used for the assay of TA-4: the positive ratio was less than 50% in SCC of the oesophagus, head and neck (Table I). In addition, even in SCC of the lung, the positive ratio was low in the early stages of the disease (Mino et al, 1988) (see also Table II). The major finding in the present study is that the limitation of the diagnostic usefulness could be considerably overcome by using the new assay method of IRMA.…”
Section: Discussionmentioning
confidence: 60%
“…The positive ratios assessed as the percentage of patients with serum TA-4 higher than the normal range were, for example, 75% and 59% in SCC of the uterus and the lung, respectively. However, as reported previously (Mino et al, 1988), its diagnostic usefulness seemed rather limited in SCC of other organs, such as the oesophagus, head and neck. This was confirmed in the present study when the conventional RIA method was used for the assay of TA-4: the positive ratio was less than 50% in SCC of the oesophagus, head and neck (Table I).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…7 Several studies have shown that increased serum SCCA levels are seen in SCC patients 8,9 and correlate with the extent of disease in patients with SCC, 10,11 although the protein itself is not detected in adenocarcinomas. 6 In a previous study, it was reported that this tumor marker could be separated into two fractions (a neutral form and an acidic form).…”
Section: Introductionmentioning
confidence: 99%